Design of a subframe to integrate an electric drivetrain in existing vehicles: Aufbau eines Subframes für die Implementierung eines elektrischen Antriebsstranges in bestehende Fahrzeuge. Issue 4 (May 2015) - Hitzler, L.; Merkel, M.; Freytag, P.
Abstract : The global efforts on CO2 emission reduction reflect the importance of a change in personal mobility. Nowadays there is a need in the automotive sector to focus more and more on ecological energy sources. One key to approach this intention is to transfer the modular manufacturing, as known in the conventional car design, to the design of electric powered vehicles. Taking into account that renewable energy sources, for example hydrogen, green electric power or fuel produced out of plants, are able to be combined with an electrical drivetrain, which is able to handle all of them in once. The impressive opportunity is that all those energy sources have a commonality. All of them can be used to produce electrical power onboard. The easiest way seems to be the storage of electrical power in rechargeable batteries; however there are various different options. Hydrogen can be utilized in a fuel cell to produce electrical power and every hydrocarbon fuel can also be used to power a fuel cell in combination with a previous steam reformation. Considering hydrocarbon fuel, there is further the alternative to burn it in combustion engines and to combine it with a generator. The perspective of this short excursus is that it does not depend on the chosen energy resource, because there is always the option to use the energy, to power an electrical drivetrain. This assumption leads to the encouragement to develop a modular and scalable electric driven axle, which is easily adaptable to ensure a compatibility with a brought field of vehicles.